Driving and dementia: An "emotionally‐charged" issue for people with dementia and their multidisciplinary healthcare providers. (1st February 2022) - Naglie, Gary; Stasiulis, Elaine; Sandhu, Harvir; Brookes, Jahnel; Vrkljan, Brenda; Mariano, Claudia; Gelinas, Isabelle; Byszewski, Anna; Rapoport, Mark; ,
Abstract: Background: The decision to stop driving and the transition to non‐driving is emotional and challenging not only for people with dementia (PWD) and their family members, but also for healthcare providers (HCPs) of multiple disciplines. With the growing number of older drivers, including drivers with dementia, HCPs are being increasingly tasked with addressing driving cessation issues. However, research indicates that most HCPs lack the knowledge, skills and resources to support PWD and their families in this context, often resulting in their avoidance of this issue. Our objective was to explore HCPs' perspectives on the content they deemed important to include in an e‐learning program being developed to educate HCPs about dementia and driving. Method: In‐depth semi‐structured interviews were conducted with 22 HCPs, including six primary care physicians, three geriatricians, three geriatric psychiatrists, six nurse practitioners and four occupational therapists practicing in six Canadian provinces. Participants were asked to provide feedback on the proposed content outline of an e‐learning program. Data were examined using a qualitative thematic analysis approach. Results: Participants emphasized the "emotionally‐charged" nature of driving cessation, which they identified as being extremely challenging for PWD, their families and for HCPs. The trauma and negative impact that driving cessation has on PWD also affects HCPs' emotions and work stress, influencing how they navigate driving cessation with their patients/clients. Further contributing to some HCPs' stress was a lack of knowledge and confidence about determining when drivers were unsafe to drive and how to support them through the transition to non‐driving. Protecting the therapeutic relationship was a primary concern for HCPs, which they managed by: 1) employing avoidance and referral practices; and 2) mitigating PWD's and family members' emotional responses via communication strategies (e.g. deep understanding, prepared scripts, early and on‐going discussions about driving). Conclusion: Study results highlight the importance of addressing the inter‐related emotional aspects of driving cessation for both PWD and HCPs in educational programs directed to HCPs.